Exosome Hypoxic-MSCs, Glutathione, and Vitamin C: Effect on IL-10 Levels and CD-163 Expression - Utami, Wulan Dyah; Muhar, Adi Muradi; Sumarawati, Titiek; Putra, Agung; Setiawan, Eko; Ibrahim, Sugeng; Taskworo, Dodik; Haitamy, Mohammad Nurrizki (Indonesian Journal of Pharmaceutical Science and Technology, 2025)
Hyperpigmentation of the skin is a result of ultraviolet B (UVB) exposure, which causes oxidative stress due to increased reactive oxygen species (ROS), leading to various skin problems, including melanin accumulation. Exosomes can affect melanocyte activity. Exosomes, as small vesicles released by cells, can affect melanocyte activity and play an important role in various hyperpigmentation processes. The study aims to determine the effect of exosome mesenchymal stem cell hypoxia (EH-MSC) and glutathione with vitamin C on IL-10 levels and CD163 expression. IL-10 gene expression was measured using qRT-PCR, while CD163 expression was analyzed via immunohistochemical staining. A total of 30 male C57BL/6 mice were used and randomly assigned to five different treatment groups. The highest expression of IL-10 was observed in the EH-MSCs-treated group (K4), although the difference was not statistically significant compared to the control (p = 0.135). In contrast, the group receiving a combination of EH-MSCs with glutathione and vitamin C (K5) exhibited the highest percentage of CD163 expression, with a statistically significant difference (p = 0.00). These findings demonstrate that the administration of EH-MSC and glutathione with vitamin C significantly increased the expression of CD163, but insignificantly increased IL-10 in C57BL/6 mice with a UVB-induced hyperpigmentation model.